2019
DOI: 10.1053/j.gastro.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Events Within the First Year of Life, but Not the Neonatal Period, Affect Risk for Later Development of Inflammatory Bowel Diseases

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e18 (https://www. gastrojournal.org/cme/home). Learning Objective: Upon completion of this CME activity, successful learners will be able to evaluate a risk paradigm for the development of inflammatory bowel disease (IBD) in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 20 publications
0
42
1
Order By: Relevance
“…According to a systematic review by Cholapranee et al, there is an inverse association between bedroom sharing, number of siblings, and the risk of IBD [29]. In support of the "hygiene hypothesis" a recent population-based study [30] on 825 IBD cases and 5999 matched controls found that being in the highest socioeconomic quintile at birth increased risk of developing IBD at some point in life. The same study found that early-life infections and the presence of a mother affected by IBD increased the risk of developing IBD later in life.…”
Section: Previous Literaturementioning
confidence: 99%
“…According to a systematic review by Cholapranee et al, there is an inverse association between bedroom sharing, number of siblings, and the risk of IBD [29]. In support of the "hygiene hypothesis" a recent population-based study [30] on 825 IBD cases and 5999 matched controls found that being in the highest socioeconomic quintile at birth increased risk of developing IBD at some point in life. The same study found that early-life infections and the presence of a mother affected by IBD increased the risk of developing IBD later in life.…”
Section: Previous Literaturementioning
confidence: 99%
“…However, the detailed composition varies regionally and individually according to the traditional diet, lifestyle, and environment [ 34 ]. Before stabilization, the microbiome is in flux and highly susceptible to disruption by external factors, such as infection, antibiotics or diet [ 36 , 37 ].…”
Section: Establishment Of the Microbiomementioning
confidence: 99%
“…Recently, our study from Manitoba, published in Gastroenterology, reported that the strongest risk factor for a child ultimately developing IBD was the presence of IBD in their mothers. 7 This factor may be genetic-the mother passing on genes that modulate how metals are handled, genes that modulate the developing gut microbiome, or both. Alternatively, this factor may be environmental-the mother passing on to the child what she is ingesting.…”
mentioning
confidence: 99%